2001
DOI: 10.1021/cm000747o
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylaminofluorene-Based Two-Photon-Absorbing Chromophores with Various π-Electron Acceptors

Abstract: A new series of linear, asymmetrical diphenylaminofluorene-based chromophores (AFX) with various strong π-electron acceptors were synthesized and evaluated for two-photon absorptivity. These chromophores were studied to determine a suitable replacement for 2-(4-vinyl)pyridine, the π acceptor for our previously reported AFX series, which contains a photochemically and thermo-oxidatively unstable olefinic unit. In addition to the benzoyl group (AF-370), these π-electron acceptors include 2-benzothiazolyl (AF-240… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
190
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(193 citation statements)
references
References 40 publications
2
190
0
1
Order By: Relevance
“…[9][10][11] Furthermore, the heteroaromatic rings are directly boned to a donor to facilitate maximal coplanarity between the donor and the acceptor, which is crucial for the efficient charge transfer in the molecules. 12 Phenothiazines have been intensively investigated as a donor in electrogenerated chemiluminescence (ECL) systems, because of their highly stable radical cations, unique nonplanar geometry, and low reversible oxidation potential. 13,14 The studies of OLEDs based on phenothiazinecontaining D-A molecules have already been reported.…”
mentioning
confidence: 99%
“…[9][10][11] Furthermore, the heteroaromatic rings are directly boned to a donor to facilitate maximal coplanarity between the donor and the acceptor, which is crucial for the efficient charge transfer in the molecules. 12 Phenothiazines have been intensively investigated as a donor in electrogenerated chemiluminescence (ECL) systems, because of their highly stable radical cations, unique nonplanar geometry, and low reversible oxidation potential. 13,14 The studies of OLEDs based on phenothiazinecontaining D-A molecules have already been reported.…”
mentioning
confidence: 99%
“…Excess dibromide was separated from product by column chromatography on silica gel with hexane as eluent and the product was eluted with ethyl acetate/ hexane (1:20). Evaporation of the solvent gave the title compound 9 (4.42 g, 60 %) as a white solid, 35 4,4'-(12,12'-Disulfanediylbis(dodecane-12,1-diyl)bis(oxy))dibenzaldehyde (10). Hexamethyldisilathiane [(Me 3 Si) 2 S] (0.435 g, 2.5 mmol) was added to the stirred solution of 4-(12-bromododecyloxy)benzaldehyde 9 (0.740, 2 mmol) in dry THF (10 mL) at -10 °C.…”
Section: -[(E)-2-(benzo[d]thiazol-2-yl)vinyl]benzaldehyde (5)mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] The benzothiazolyl unit is an excellent acceptor that gives rise to donor-π-acceptor (D-π-A) type compounds. [10][11][12] Benzothiazolyl derivatives have much better chemical, thermal, and photochemical stabilities than structurally similar compounds. 10 2-(3,5,6-Trifluoro-2-hydroxy-4-methoxyphenyl) benzothiazole with a zinc cation is used for fluorescent probe sensing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributed by many scientists and research groups, numerous Type II and some Type III MPA active compounds were successfully synthesized [16][17][18][19] and characterized in the past two decades as investigation of MPA structureproperties relationship. The π-bridges could be unsaturated aliphatic chains or aromatic ring which connected the acceptor(such as: triazine, triphenylamine) and donors (such as, nitrogen-containing heterocyclic aromatic groups).…”
Section: Introdutionmentioning
confidence: 99%